Science E-Book Development Using Project-Based Learning (PjBL) Model Integrated with Pancasila Student Profile - Sumarni Sahjat; Nurlaela Muhammad; Iqbal Limatahu; Aji Saputra (Jurnal Penelitian Pendidikan IPA, 2025)
The rapid advancement of technology has led students to prefer digital learning materials over traditional textbooks. However, at SMP Negeri 1 Kota Ternate, science teaching materials remain limited to conventional textbooks, with minimal integration of digital resources. This study aims to develop a science e-book utilizing the Project-Based Learning (PjBL) model integrated with the Pancasila Student Profile to enhance student engagement and understanding. Employing a Research and Development (R&D) approach, the study followed the ADDIE model, comprising analysis, design, development, implementation, and evaluation. The e-book was validated by two lecturers and two science teachers, with assessments focusing on content and language aspects. Results indicated an average validity score of 79%, categorizing the e-book as moderately valid. Field trials showed that students found the e-book easy to use, with practicality scores averaging 3.20 from teachers and 3.00 from students. The integration of PjBL and the Pancasila Student Profile in the e-book facilitated student-centered learning, promoting critical thinking, collaboration, and creativity. These findings suggest that the developed science e-book is a suitable and effective digital learning resource for enhancing science education at the secondary level.